Fractionation of liquid products from pyrolysis of lignocellulosic biomass by stepwise thermal treatment. (1st July 2018) - Persson, H.; Han, T.; Sandström, L.; Xia, W.; Evangelopoulos, P.; Yang, W.
Abstract: The thermal properties of cellulose, hemicellulose and lignin can be utilized to improve the characteristics of pyrolysis liquids. In this study, a concept of stepwise pyrolysis to fractionate the liquid based on the thermal properties of the biomass constituents was investigated. Lignocellulosic biomass was thermally treated in two steps: 200–300 °C followed by 550 °C. Derived liquids were studied for GC/MS analysis, water content, acid concentration and a solvent extraction method. Pyrolytic liquid derived from 550 °C after treatment at lower temperatures have a higher relative composition of phenolic compounds compared to one-step pyrolysis (increased from 58 to 90% of GC/MS peak area). Also, compounds known to promote aging, such as acids and carbonyl compounds, are derived at lower temperatures which may suppress aging in the liquid derived downstream at 550 °C. For liquids derived at 550 °C, the total acid number was reduced from 125 in one-step treatment to 14 in two-step treatment. Overall, no significant difference in the total liquid yield (sum of the liquids derived in separated treatments) nor any variations in their collective composition compared to one-step treatment at 550 °C was observed, i.e. stepwise pyrolysis can be utilized for direct fractionation of pyrolytic vapors. Highlights: Bio-oil is fractionated through pyrolysis without changing its total composition. Stepwise treatment does not reduce the liquid yield compared to one-step pyrolysis. Acid concentration is reduced at higher temperatures in stepwise treatment. Main part of organic liquid from PKS is produced at 300 °C.